PERUBAHAN KIMIA KAYU PADA GUBAL GAHARU (Aquilaria malaccensis Lamk.)HASIL REKAYASA) (Wood Chemical Changes In Gubal Agarwood (Aquilaria malaccensis Lamk.) Engineered) - Chendy Herawati; Ridwanti Batubara; Edi Batara Mulya Siregar (Program studi Kehutanan USU, 2013)
Indonesia is the biggest producer gaharu (A. malaccensis Lamk.) in the world with the best quality. Agarwood is elite commodity non timber forest products that have potential as an industrial raw material The research objective is measuring physical properties (water content and density) of wood tissue is induced to form the agarwood. Measuring changes in the chemical content (hemicellulose, cellulose, alpha cellulose and lignin) of wood tissue induced 12 months, 6 months, and the control of long induced agarwood. Treatment in research was induced period of 6 months, 12 months and control. The analysis was done according to ASTM Standard D 4933-99 and TAPPI. The result of research showed that the induced agarwood for 12 months had a higher density than the control, and 6 months. while the water content was not significanctly different. The extractive substances that contained in induced agarwood had a higher value than the control (the value of agarwood solubility in cold water, solubility in hot water, solubility in NaOH, solubility in alcohol and benzene). The content of hemicelluloses, cellulose and alpha cellulose in the induced agarwood for 12 months trend to be lower than the control. Keyword: agarwood, A malaccensis Lamk., physical properties, chemical properties, induced